A Role for the Inflammasome in Spontaneous Labor at Term with Acute Histologic Chorioamnionitis. (June 2017) - Gomez-Lopez, Nardhy; Romero, Roberto; Xu, Yi; Plazyo, Olesya; Unkel, Ronald; Than, Nandor Gabor; Chaemsaithong, Piya; Chaiworapongsa, Tinnakorn; Dong, Zhong; Tarca, Adi L.; Abrahams, Vikki M.; Yeo, Lami; et al.
Inflammasomes are cytosolic signaling platforms that regulate the activation of caspase (CASP)-1, which induces the maturation of interleukin (IL)-1β and IL-18. Herein, we determined whether the chorioamniotic membranes from women in spontaneous labor at term with acute histologic chorioamnionitis express major inflammasome components and whether these changes are associated with the activation of CASP-1 and CASP-4 and the release of mature IL-1β and IL-18. When comparing the chorioamniotic membranes from women in spontaneous labor at term with acute histologic chorioamnionitis to those without this placental lesion, we found that (1) the messenger RNA (mRNA) abundance of NLR family pyrin domain containing 3 ( NLRP3 ), NLR family CARD domain containing 4 ( NLRC4 ), absent in melanoma 2 ( AIM2 ), and nucleotide binding oligomerization domain 2 ( NOD2 ) was higher; (2) the NLRP3 and NLRC4 protein quantities were increased; (3) the mRNA and protein expressions of CASP-1 and its active forms were greater; (4) CASP-4 was increased at the mRNA level only; (5) the mRNA and protein expressions of IL-1β and its mature form were higher; and (6) a modest increase in the total protein concentration and abundance of the mature form of IL-18 was observed. In vitro incubation of the chorioamniotic membranes with the CASP-1 inhibitor, VX765, decreased the release of endotoxin-induced IL-1β and IL-18 (2-fold) but not IL-6 or tumor necrosis factor α. In conclusion, spontaneous labor at term with acute histologic chorioamnionitis is characterized by an upregulation of inflammasome components which, in turn, may participate in the activation of CASP-1 and lead to the release of mature IL-1β by the chorioamniotic membranes. These results support a role for the inflammasome in the mechanisms responsible for spontaneous labor at term with acute histologic chorioamnionitis.